Within- and cross-country price dispersion in the euro area - Adam Reiff; Fabio Rumler (European Central Bank (ECB), 2014)
Using a comprehensive data set on retail prices across the euro area, we analyse within- and cross-country price dispersion in European countries. First, we study price dispersion over time, by investigating the time-series evolution of the coefficient of variation, calculated from price levels. Second, since we find that cross-sectional price dispersion by far dominates price dispersion over time, we study price dispersion across space and investigate the role of geographical barriers (distance and national borders). We find that (i) prices move together more closely in locations that are closer to each other; (ii) cross-country price dispersion is by an order of magnitude larger than within-country price dispersion, even after controlling for product heterogeneity; (iii) a large part of cross- country price differences can be explained by different tax rates, income levels and consumption intensities. In addition, we find some indication that price dispersion in the euro area has declined since the inception of the Monetary Union.
Keywords: E31; F41; 330; border effect; international relative prices; price dispersion